SISTEM INFORMASI MANAJEMEN ASET BERBASIS WEB DI UNIVERSITAS TEKNLOGI SUMBAWA - M. Zayyan Musoffa; Eri Sasmita Susanto; Yudi Mulyanto (Program Studi Informatika Universitas Teknologi Sumbawa, 2022)
Sumbawa University of Technology is one of the universities in West Nusa Tenggara which is located in the village of Pernek, Moyohilir District, Sumbawa Regency. Sumbawa University of Technology owns a building, and has many assets that have not been digitized and asset management is still done by filling in data in Microsoft Word and Microsoft Excel, data entered such as asset procurement, asset location, asset data written off, and asset data that has experienced depreciation. all felt less effective and efficient. So we need a system that accommodates all of these needs. This study uses a qualitative approach and the software development method used is the System Development Life Circle (SDLC) spiral model and the black-box test method. The process of modeling and designing the system is done by object using the Unified Modeling Language (UML). The conclusion of this research is to produce a Web-Based Asset Management Information System at the Sumbawa Technology University which is able to facilitate the management of Sumbawa Technology University's assets to be more effective and efficient